Overstress Avoidance on Flexible Object Manipulation - Zafra Navarro, Alberto; Aragüés Muñoz, Rosario; López Nicolás, Gonzalo (Jornada de Jóvenes Investigadores del I3A, 2025)
Handling deformable objects remains a major challenge due to the complex physics involved. This work presents an enhanced multirobot control system that incorporates a physically-safe control barrier function. This system ensures the structural integrity of deformable objects during manipulation, by using a finite element analysis. The proposed method dynamically adjusts control actions to avoid overstressing configurations.